Human, the Electric Machine - Anurag Pandey (Institute of Advanced Engineering and Science, 2016)
In modern time we are using lot of electronic devices but to run an electronic unit power generation is taking place. Major issue is it also generating problem of pollution. So, an effort has been made to harvest energy from human body for power supply. In this paper different method of energy harvesting from human body such as thermo electric power, power from heartbeat, angular knee and footsteps motion are briefly reviewed and showed that how principle of thermo electric power may be helpful to reduce abnormal level of β brain wave, caused due excessive stress and/or anxiety. An automation system can be used to control these generated power. This paper also presents a ladder logic algorithm to control for human generated power using PLC programming, with RS-232 DF1interface.